Synthesis, Characterisation and Applications of Zirconium Phosphate Nanocomposite Ion Exchange Material - Neeraj (My University, 2017)
Zirconium Phosphate (ZrP) based ion exchangers were prepared and modified with CNT of different concentration (ZrP-CNT). Different concentration of CNT ranging from 0.01% to 0.1% were incorporated in the framework of ZrP. Ion exchange capacity of each of the prepared ion exchanger was tested and found that 0.1% CNT based Zirconium Phosphate nanocomposite has higher value. Furthur, thermal stability and chemical stability studies were also performed. It was found that ZrP-CNT material retain its structure even at higher temperature i.e. at 400 oC and have good chemical stability in strong acids, salt solutions, organic solvents except in NaOH solution. Potentiometric titration of ZrP and ZrP-CNT nanocomposites suggests that they are weakly acidic in nature.
Keywords: Nanocomposite; Zirconium phosphate; Ion exchange material